Tiresias and the Basilisk: vision and madness in Middleton and Rowley’s The Changeling - Stott, Andrew (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1999)
This essay examines the prevalent and recurring references to vision and sight that appear in Thomas Middleton and Samuel Rowley's play of 1622, The Changeling. The play, set in Alicante, is a revenge tragedy of sexual lust and violent obsession. Middleton and Rowley use the metaphors of sight, culled and adapted from the Petrarchan tradition, as a means of expressing evil, danger, and deceit, particularly when the viewing subject is female. There follows an examination of the reasons for gendering vision and expressing the visual field in this wholly negative way. Following the Protestant reformation of the 1530s, and its violent consolidation under the Somerset protectorate, England experienced a period of iconoclasm and image breaking that had significant repercussions for concepts of vision and visuality up until the Civil War. The language of The Changeling, it is argued, is symptomatic of the iconophobia and visual neuroses experienced in many areas of discourse -including poetry, theology and theology- during the English renaissance. Finally, these ideas are brought together in two figures invoked by the authors, the basilisk, the mythical creature that had the ability to kill with its gaze alone, and Tiresias, a blind prophet of profound insight.